Anti-TNF therapy for rheumatoid arthritis and other inflammatory diseases. - Taylor, P (2001)
The availability of agents that block the biological activity of tumor necrosis factor alpha (TNF alpha) in rheumatoid arthritis (RA) has permitted studies that confirm the key role of this cytokine in the pathogenesis of this disease. To date, two anti-TNF agents, infliximab and etanercept, have been approved for use in treatment. Clinical trials of these agents demonstrate efficacy for the control of symptoms and signs and acceptable safety in patients who have failed to respond adequately to conventional therapy. Combination with methotrexate appears to be particularly effective and may provide the main initial indication for clinical application in the first instance. Repeated administration of anti-TNF therapies over a one year period results in sustained reduction in symptoms and signs of RA in the majority of patients. It has recently become apparent that anti-TNF therapy protects joints from structural damage. These findings imply that TNF alpha has a critical role in the bone and cartilage damage associated with RA. Evidence to date support the hypothesis that there are 2 particularly important mechanisms of action; deactivation of the proinflammatory cytokine cascade at the site of inflammation and diminished recruitment of inflammatory cells from blood to the rheumatoid joint.